2010
DOI: 10.1093/pcp/pcq056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Profiling of a Salt-Tolerant Wild Tomato Species and a Salt-Sensitive Tomato Cultivar

Abstract: Wild halophytic tomato has long been considered as an ideal gene donor for improving salt tolerance in tomato cultivars. Extensive research has been focused on physiological and quantitative trait locus (QTL) characterization of wild tomato species in comparison with cultivated tomato. However, the global gene expression modification of wild tomato in response to salt stress is not well known. A wild tomato genotype, Solanum pimpinellifolium 'PI365967' is significantly more salt tolerant than the cultivar, Sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 51 publications
8
138
1
3
Order By: Relevance
“…Monforte et al (1997) reported that salt tolerance in S. pimpinellifolium accessions (L1 and L5) is characterized by higher fruit number, total fruit weight and mean fruit weight under saline condition, which is controlled by several QTLs with epistatic and heterotic effects. In contrast, Sun et al (2010) reported that salt tolerance in a S. pimpinellifolium accession (PI365967) is characterized by higher survival rate, lower growth inhibition at the vegetative stage and less accumulation of sodium in shoots with the activation of salicylic acid pathway related genes.…”
Section: Discussionmentioning
confidence: 95%
“…Monforte et al (1997) reported that salt tolerance in S. pimpinellifolium accessions (L1 and L5) is characterized by higher fruit number, total fruit weight and mean fruit weight under saline condition, which is controlled by several QTLs with epistatic and heterotic effects. In contrast, Sun et al (2010) reported that salt tolerance in a S. pimpinellifolium accession (PI365967) is characterized by higher survival rate, lower growth inhibition at the vegetative stage and less accumulation of sodium in shoots with the activation of salicylic acid pathway related genes.…”
Section: Discussionmentioning
confidence: 95%
“…Salt tolerance of the cultivated tomato can be significantly enhanced by over-expressing an NHX-type Na + /H + antiporter localized to the vacuolar membrane which enables plants to compartmentalize Na + in the vacuole (Yarra et al, 2012). Comparative transcriptomic profiling of the salt-tolerant S. pimpinellifolium 'PI365967' and the salt sensitive tomato cultivar Moneymaker revealed that a gene encoding SA binding protein 2 (SABP2), which functions in converting methylsalicylate into SA, was induced by salinity only in the wild species (Sun et al, 2010). Genes coding for plasma membrane ATPase1, cell wall peroxidase and cytosolic APX as well as lactoylglutathione lyase involved in methylglyoxal detoxification were up-regulated only in 'PI365967', but other peroxidases and glutathione S-transferases (GSTs) were induced in Moneymaker under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Such a strategy mainly relies on comparative transcriptome analysis [20] using microarrays. A plethora of comparisons between salt-sensitive and salt-tolerant cultivars of model and non-model plant species such as Arabidopsis [21][22][23], rice [24], tomato [25], poplar [26], potato [27] and sugarcane [28] have been reported up to now. These reports resulted in the identification of more than 30 families of transcription factors comprising DREB, CBF, MYB, bZIP and zing-finger families which are involved in abiotic stress including salinity [29,30].…”
Section: Introductionmentioning
confidence: 99%